Study of the formation of ferrihydrite under prebiotic chemistry conditions: artificial seawater 4.0 Gy and ammonium thiocyanate. Issue 6 (15th December 2020) - Zaia, Dimas A. M.; Coutinho, Murilo A.; Mosca, Dante H; da Costa, Antônio C. S.; Urbano, Alexandre
Abstract: Among the several steps involved in molecular evolution, molecular preconcentration is the first and most important. If the molecules are not preconcentrated the other steps of molecular evolution cannot occur. There are several ways to preconcentrate molecules: sorption, wetting/drying cycles, freezing/sublimation and sorption/precipitation with minerals. In the present work, the effect of NH4 SCN and artificial seawater 4.0 Gy on the synthesis of ferrihydrite was studied. It should be noted that thiocyanate could play the same role as that of CN − in the Strecker reaction. Unlike today's seawater that has high Na + and Cl − concentrations, the seawater used in this work has high Mg 2+, Ca 2+ and SO4 2− concentrations. Two results stand out, first SCN − and NH4 + were preconcentrated by sorption/precipitation in some syntheses and second, in some experiments, a mixture of goethite, hematite and magnetite was obtained. The sorption/precipitation of SCN − is always associated with the synthesis of goethite. This could be an indication that SCN − interacts with Fe 3+ through the sulphur group of SCN − . In addition, the synthesis of magnetite could be an indication that the SCN − ion oxidized, forming thiocyanogen-(SCN)2 or trithiocyanate ion-(SCN) − 3 and that Fe 3+ reduced to Fe 2+ . Besides the sorption/precipitation of SCN − and NH4 +, Fourier-transform infrared spectroscopy also showed that sorption/precipitation of SO4 2− and CO3 2− occurred. Ferrihydrite synthesized with artificial seawater presented the highest surface area and pore size. The pHpzc values of the samples were in the range of pHpzc described in the literature. The X-ray photoelectron spectroscopy (XPS) measurements performed show proportions of iron present in different oxidation states, however, the electronic similarities observed in the mixtures of iron oxides and oxy-hydroxides make it difficult to quantify them. Direct comparison between XPS spectra of the Fe2p and O 1s core-levels reveal no significant differences from the effect of artificial seawater 4.0 Gy on the synthesis of ferrihydrite.